Fixed Cost Magnitude, Fixed Cost Reporting Format, and Competitive Pricing Decisions: Some Experimental Evidence* - BUCHHEIT, STEVE (Contemporary Accounting Research, 2004)
Although neoclassical economic theory predicts that fixed cost magnitude and fixed cost reporting format will not influence short‐term pricing decisions, these factors systematically affected pricing decisions in a duopoly experiment. Increasing fixed cost magnitude (a pure sunk cost in this study) across experimental conditions caused participants to first lower, then raise, competitive prices. Consistent with the psychological phenomenon of loss aversion, this change in pricing behavior reduced the frequency of reported losses. This study further reveals that the accounting format for reporting fixed costs influenced pricing behavior. Specifically, participants receiving capacity costing feedback reports established increasingly lower selling prices relative to the prices established by participants receiving contribution margin feedback reports. Given that a very simple cosmetic reporting manipulation produced increasingly significant competitive pricing differences in a market setting, this study provides evidence that functional fixation is not necessarily eliminated by market forces.